The Influence of Retail Marketing Mix on Customer Satisfaction (An Empirical Study on Indomaret Pontianak)â€ - admin, OKY BASRI B12111030 (Jurnal Manajemen Update, 2016)
The increase of competitive environment in the retail sector, especially modern retail drives the retail industry to have more consideration on customer satisfaction to win the competition. One of the strategies that can be adopting and implementing to win the competition is retail marketing mix strategy. There are six elements of retail marketing mix, such as merchandise, pricing, location, retail service, promotion, and store atmosphere. The study aimed to analyze the effect of the retail marketing mix toward customer satisfaction on Indomaret Pontianak. Primary data was gathered using questionnaire base on 100 respondents of Indomaretâ€™s customers in Pontianak. The data was analyzed based on multiple linear regression analysis. The results of the study showed that two of the six elements of the retail marketing mix, i.e. retail service and store atmosphere significantly influence the customer satisfaction. Â  Keywords: retail marketing mix, satisfaction